2016
DOI: 10.1038/onc.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of tumor suppression in prostate cancer by targeting the E3 ligase E6AP

Abstract: Restoration of tumor suppression is an attractive onco-therapeutic approach. It is particularly relevant when a tumor suppressor is excessively degraded by an overactive oncogenic E3 ligase. We previously discovered that the E6-associated protein (E6AP; as classified in the human papilloma virus context) is an E3 ligase that has an important role in the cellular stress response, and it directly targets the tumor-suppressor promyelocytic leukemia protein (PML) for proteasomal degradation. In this study, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…Consistently, mice over-expressing E6AP develop enlarged prostate glands and show prostatic intra-epithelial neoplasia (18,19). Moreover, knockdown of E6AP in PC cells attenuates cellular growth in vitro and in vivo (20), further supporting an oncogenic function of E6AP in PC. We have recently demonstrated that this is partially explained by the effect of E6AP on the key tumor suppressors, promyelocytic leukemia protein (PML; (20)) and p27 (17).…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Consistently, mice over-expressing E6AP develop enlarged prostate glands and show prostatic intra-epithelial neoplasia (18,19). Moreover, knockdown of E6AP in PC cells attenuates cellular growth in vitro and in vivo (20), further supporting an oncogenic function of E6AP in PC. We have recently demonstrated that this is partially explained by the effect of E6AP on the key tumor suppressors, promyelocytic leukemia protein (PML; (20)) and p27 (17).…”
mentioning
confidence: 66%
“…Moreover, knockdown of E6AP in PC cells attenuates cellular growth in vitro and in vivo (20), further supporting an oncogenic function of E6AP in PC. We have recently demonstrated that this is partially explained by the effect of E6AP on the key tumor suppressors, promyelocytic leukemia protein (PML; (20)) and p27 (17). This in vitro and in vivo work is further supported by tissue microarray data demonstrating that patients with localized PC expressing high levels of E6AP and low levels of PML have the shortest clinical relapse-free survival and this correlation is a significant predictor of prostate cancer-associated death (21).…”
mentioning
confidence: 71%
See 3 more Smart Citations